Atomistic hybrid particle‐field molecular dynamics combined with slip‐springs: Restoring entangled dynamics to simulations of polymer melts. Issue 1 (3rd October 2020) - Wu, Zhenghao; Kalogirou, Andreas; De Nicola, Antonio; Milano, Giuseppe; Müller‐Plathe, Florian
Abstract: In hybrid particle‐field (hPF) simulations ( J. Chem. Phys., 2009 130, 214106), the entangled dynamics of polymer melts is lost due to chain crossability. Chains cross, because the field‐treatment of the nonbonded interactions makes them effectively soft‐core. We introduce a multi‐chain slip‐spring model ( J. Chem. Phys., 2013 138, 104907) into the hPF scheme to mimic the topological constraints of entanglements. The structure of the polymer chains is consistent with that of regular molecular dynamics simulations and is not affected by the introduction of slip‐springs. Although slight deviations are seen at short times, dynamical properties such as mean‐square displacements and reorientational relaxation times are in good agreement with traditional molecular dynamics simulations and theoretical predictions at long times. Abstract : The hybrid particle‐field simulation enables efficient modeling of the structural evolution of complex polymeric fluids. However, chain uncrossability is lost because of soft‐core density‐field interactions, causing incorrect dynamics of polymer melts. Introducing slip‐springs, artificially mimicking the topological constraints between polymer chains, recovers the entangled dynamical behavior of polymer melts. The structural properties of the polymer chain are observed not to be affected by the introduction of slip‐springs. This article shows improved dynamics in the hybrid particle‐field simulation of polymer melts via combining it with a multi‐chain slip‐spring model.